ANALYSIS OF THE IMPACT OF URBAN PARK DEVELOPMENT IN BATURAJA, OGAN KOMERING ULU REGENCY - Pangaribuan, Robi Binsar Hamonangan (Universitas 17 Agustus 1945 Surabaya, 2025)
Urban parks are a form of development located in urban areas that hold significant value due to their large-scale function in assisting urban spatial planning. This research is a descriptive qualitative study that aims to illustrate the social, economic, cultural, and ecological impacts resulting from the development of urban parks in Baturaja, Ogan Komering Ulu Regency. Based on data analysis and field findings, it can be concluded that urban park development is one of the elements of urban development that brings both positive and negative impacts to the communities around Baturaja City, across various sectors including Economy, Society, Culture, and Ecology. Moreover, the park contributes to enhancing social interaction among Baturaja residents, fostering a sense of pride in the local area, and serving as a reminder of the historical origins of Baturaja as the capital of Ogan Komering Ulu Regency. On the other hand, the most significant negative impact experienced by the local community from an ecological perspective is the lack of cleanliness in the urban park environment, primarily due to the community’s low awareness in maintaining the park’s cleanliness and beauty.